Study Information and Literative Culture in Pressing Hoax As A Form Of State Defense (Pancasila Actualization) in The Era Of Covid-19 - Yohanes Firmansyah; Slamet Tri Wahyudi (Jurnal Indonesia Sosial Sains, 2021)
For all countries and communities, including Indonesia, globalization is both a threat and an opportunity. Globalization is like a double-edged sword, and the very rapid development of information and communication technology is one of the greatest elements of globalization. Pancasila is a legacy of ancestral noble values extracted from the cultural values of the people of Indonesia. Cultural axiology and the principles of Pancasila are the noble values of Pancasila that can be used as a reference in the life of the nation and state. During the Covid-19 Pandemic, the application of Pancasila as the actualization of State defense was very important, particularly with regard to the culture of literacy in order to suppress hoaxes. This study is a literature review that examines the Covid-19 pandemic as a social disaster, the attitude of defending the State, the actualization of Pancasila, the two sides of State security, and the attitude of defending the State during the Covid-19 pandemic. The purpose of making this paper is to increase awareness in defending the public's state regarding the importance of literacy during the Covid-19 period. This work is based on a literature review. The literature search took place from January 1, 2021, to January 7, 2021. This study involves qualitative research, in which three types of approaches, namely: legal, conceptual, and analytical approaches, will examine in part all the materials and literature collected during the research period. The findings of this study show that covid-19 is a social disaster that attacks all aspects of human life, and one way for society to overcome the pandemic of Covid-19 is to defend the state and update the values of Pancasila in social life. In addition, one of the cultures that can be used to ward off non-military threats is Pancasila and the attitude of defending the state.